2018
DOI: 10.1155/2018/1849616
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Synthesis of Zero- and One-Dimensional, Spherical, Rod-, Needle-, and Wire-Shaped CuO Nanoparticles byProteus mirabilis10B

Abstract: Natural environment is a wealthy source of bionanofactories that invested in green approaches as the fabrication of biomimetic nanomaterials. The current study points out the importance of microbial activity in metal bioremediation, green synthesis of NPs, and global biogeochemical cycles of bioactive metals as well. It describes for the first time the synchronous biosynthesis of zero-(intracellular) and one-dimensional (extracellular) copper oxide nanoparticles (CuO-NPs) via Proteus mirabilis 10B. This bionan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 58 publications
5
22
0
Order By: Relevance
“…The EDX spectra contained mainly the elements Cu and O, with weight percentages of 62.96% and 22.93%, respectively. The presence of S may have been due to the conjugation of CuO-NPs with fungal biomolecules found in the biomass filtrate, such as amino acids (cysteine or methionine) and phospholipids [ 52 ]. In line with this, Hassan et al [ 47 ] reported that the main EDX spectra peaks for CuO-NPs synthesized by endophytic actinomycetes were Cu and O, with the presence of other minor peaks related to biomolecules in the actinobacterial filtrate, which conjugated with CuO-NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The EDX spectra contained mainly the elements Cu and O, with weight percentages of 62.96% and 22.93%, respectively. The presence of S may have been due to the conjugation of CuO-NPs with fungal biomolecules found in the biomass filtrate, such as amino acids (cysteine or methionine) and phospholipids [ 52 ]. In line with this, Hassan et al [ 47 ] reported that the main EDX spectra peaks for CuO-NPs synthesized by endophytic actinomycetes were Cu and O, with the presence of other minor peaks related to biomolecules in the actinobacterial filtrate, which conjugated with CuO-NPs.…”
Section: Resultsmentioning
confidence: 99%
“…36 However, as reaction proceeds with time, the copper (I) oxide was formed and finally CuO nanoparticles formation occur by a series of following reactions (Figure 1). [35][36][37]…”
Section: Results and Discussion Green Synthesis Of Cuo Nrs And Uv-vismentioning
confidence: 99%
“…It is the particle diffusion behavior within any fluid and is measured by the fluctuations in light intensity that passes through a colloidal solution as a function of time. 37 Further, zeta potential is considered as a measure of charges on the surface of nanoparticles. It indicates the stability of colloidal dispersions.…”
Section: Results and Discussion Green Synthesis Of Cuo Nrs And Uv-vismentioning
confidence: 99%
“…Such naturally motivated technology addresses the art of designing materials in nanostructure configuration (less than 100 nm, at least in one dimension) that exhibit unique features surpassing their bulk-counterparts 1 , 2 . Over the recent decade, the paradigm leapfrogging in nanotechnology has led to an improvement in the methods of synthesizing nanomaterials that included the employment of green chemistry approaches 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%